Studi Kasus : Asuhan Keperawatan pada Pasien dengan HIV Stadium 1 di Rumah Sakit Daerah Gunung Jati Kota Cirebon - Endah Sari Purbaningsih; Muadi Muadi; M. Haikal A.A; Risca Meliana S (Lembaga Pengembangan Kinerja Dosen, 2023)
Human Immunodeficiency Virus (HIV) is one of the retro viruses that infects white blood cells which has an impact on a weakened immune system, damage to the function of cluster of differentiation 4 positive (CD4+) cells as well as other immune cells. CD4 count below 200, opportunistic infections and not taking treatment can exacerbate chronic conditions throughout life. The purpose of this study was to analyze nursing care for Mr. B with Stage 1 HIV at the Seroja Polyclinic, Gunung Jati Hospital, Cirebon City. The research design used was a descriptive case study including assessment, data analysis, nursing diagnoses, interventions, implementation and evaluation. This research was conducted in the seroja room of Gunung Jati Hospital, Cirebon City. Based on the results obtained, based on the assessment data, two nursing problems emerged, namely hyperthermia, related to the disease process marked by fever and secondly the risk of opportunistic infections associated with decreased immune system which was marked with a CD4 value close to 200. Actions taken were monitoring body temperature and collaborating on drug administration with doctors, providing health education about HIV, adherence to taking medication and advising regular eating patterns and adequate rest. It is recommended that health workers provide education about HIV/AIDS care and also provide medication taking assistance to prevent non-adherence in taking medication, social and spiritual.